The impact of broker's recommendations in Kuala Lumpur stock exchange (KLSE) - Pui, Wan Bing (Universiti Malaysia Sarawak, (UNIMAS), 2003)
This study empirically examines the impact of stock recommendations produced by a stockbrocking firm from Singapore on the equity market in Malaysia. This comparative study was conducted on 159 recommended stocks and randomly selected stocks from the Kuala Lumpur Security Exchange (KLSE) stock market spanning over a recent 1-year period. Two questions are addressed namely do broker's recommendations ahve predictive ability and do broker's recommendations generate abnormal return? Using event study methodology, buy, sell and hold type recommendations are observed to have a significant impact on stock prices in the post-recommendation period. Statistical analysis such as t-test was carried out to test the research hypotheses